Implikasi Sengketa Batas Wilayah Terhadap Penyelenggaraan Pemilu (Studi Kasus di Provinsi Maluku Utara) - Sultan Alwan (Jurnal Selat, 2020)
Area expansion as a consequence of regional autonomy implementation has caused excess regional boundary disputes which led to conflicts. The case that occurred in six villages in the North Maluku Province was due to the refusal of residents to be part of the District in North Halmahera Regency and wanted to remain in the West Halmahera Regency. In reality there is a dualism in government administration services because each village has two Village Heads, namely the North Halmahera government and the West Halmahera government version. The dissolution of disputes settlement has implications for the implementation of Regional Head Elections and Elections in the region. Election Organizers stipulate that the Permanent Voters List (DPT) of six villages is included in the jurisdiction of North Halmahera Regency. As a form of protest, thousands of citizens did not exercise their right to vote in the 2014 and 2018 Regional Head Elections. The General Election Law and Regional Head Election at present, it has not explicitly regulated the guarantee of the protection of citizens’ rights to vote in the area of boundary disputes due to the division of regions. In the future, special arrangements need to be made so that no citizen loses his right to vote because of technical administrative issues that ignore the election substance.